Common Themes in RNA Subcellular Transport, Stress Granule Formation and Abnormal Protein Aggregation - Benseñor, Lorena Betsabe (2011)
Control of protein synthesis and quality are critical steps to support eukaryotic cells’ maintenance and survival. Two very distinctive mechanisms emerge as key checkpoints of protein synthesis regulation. The first one is the delivery of mRNA molecules, packed into ribonucleoprotein (mRNP) granules, to specific subcellular regions in order to restrict protein synthesis to distinct cytoplasmic domains. In the presence of cellular stress or injury, translation is aborted by sequestering mRNA molecules into a sub-type of RNP particles called stress granules (SGs). The second mechanism deals with the folding state and further processing of synthesized proteins. Misbehavior of a particular protein, affecting its processing, functioning, and/or conformation can cause the formation of protein inclusions called aggresomes. Interestingly, self-aggregation of abnormal proteins is one of the leading causes of neurodegenerative disorders. Recently, intracellular transport directed by microtubule-motors, has emerged as an important step in the assembly and dynamic of SGs and aggresomes. This mechanism allows for a precise temporal and spatial trafficking of RNA and protein complexes. Furthermore, it facilitates the regulation of the RNA silencing domains and targets abnormal protein aggregates for degradation. In this review we will explore the specific and common features of mRNA transport and of SG and aggresome formation, and will provide details on the role of the microtubule network and motors in their movement and dynamics.